NATURE-BASED SOLUTIONS AS URBAN CLIMATE ADAPTATION TOOLS FOR ARMENIAN CITIES (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The ongoing process of urbanization significantly affects environmental quality, particularly in the context of global climate change. The Republic of Armenia (RA) is no exception, as urban development continues without strategic planning, leading to adverse impacts on the urban microclimate and reducing resilience to the negative effects of climate change. Drawing on international experience in implementing nature-based solutions (NbS) in urban areas, this study aims to demonstrate their potential, as well as the feasibility and effectiveness as key climate adaptation tools for urban settlements in Armenia using case studies, expert interviews, and policy analysis. However, the effective implementation and advancement of NbS are hindered by limited knowledge and experience, as well as the absence of a strategic approach and an adequate legal framework for their integration into the urban planning process.
Keywords: nature-based solutions; climate change; urban heat island; climate adaptation; urban resilience